If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7f + 1 = 9 + 6f Reorder the terms: 1 + 7f = 9 + 6f Solving 1 + 7f = 9 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. 1 + 7f + -6f = 9 + 6f + -6f Combine like terms: 7f + -6f = 1f 1 + 1f = 9 + 6f + -6f Combine like terms: 6f + -6f = 0 1 + 1f = 9 + 0 1 + 1f = 9 Add '-1' to each side of the equation. 1 + -1 + 1f = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 1f = 9 + -1 1f = 9 + -1 Combine like terms: 9 + -1 = 8 1f = 8 Divide each side by '1'. f = 8 Simplifying f = 8
| 270=10x+100 | | 35=30 | | Z=7 | | -3+9v=-2+8v | | 7c+5=5+7c | | -10s+10=-9s | | 9a+6.75c=1406.25 | | 12=5x+13x-44 | | 4y^2-23y-6=0 | | 3(2m-5m)= | | -6q=-5q-8 | | 4(2n+3)=6(5n+8)+2 | | 1-10g=-10g+1 | | 9a+6.75c= | | 0.13333333333x=20 | | 0.13333333333x=14 | | 4t-15=6t-2 | | 2x-5(x-3)=-6+2x-14 | | 3x+8-9x=-4 | | 7=5a-12 | | -3(-2x+5y)+5(-x+4y)= | | -9r=-9r-10 | | 32x^2-98= | | 2x-5(x-3)=-6+2-14 | | -35=-8+3y | | -45x^2+33x-6= | | 3n=5n-2n | | 5m+9=1+4m | | 12-5a=30 | | 35-X=x | | 8=2+12 | | 22+2x=x-4 |